METODE PEMBELAJARAN ANAK USIA DINI DALAM GENERASI UNGGUL DAN SUKSES - Siswanto Siswanto; Zaelansyah Zaelansyah; Eli Susanti; Jeni Fransiska (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2019)
This research aims to determine whether the meaning of early childhood education and what methods are used for early childhood. Early childhood education is the right time to lay the foundation for physical abilities, language, social emotional, self-concept, art, moral and religious values. So that efforts to develop the full potential of early childhood should begin so that the child's growth and development are optimally achieved, this must be in accordance with the methods / methods used at that age so that the child does not become bored. The study uses a qualitative research and qualitative descriptive approach. The method of retrieving data by observation and interview, and then analyzed. Next the result is early childhood education, namely children newly born until the age of 6 years. The learning process at this age really determines the formation of character and personality of children. Furthermore, teaching at RA IPKB, the teaching methods in PAUD are playing, telling stories, singing, talking, field trips and hands-on practice. Because of the teaching for early childhood at RA IPKB, I think it is feasible, because not only general knowledge is obtained, but children's religious knowledge is also learned. Thus children can compete later in high school which is not only intellectuals that can be obtained, but also spiritually owned.